Enterprise Mortgage – the Feature of the Modern Secured Transaction Law? - Juzikienė, Renata (Teisė, 2018)
The article analyzes advantages and drawbacks of the mortgage enterprise, as the form of commercial charge of the widest scope. The drawbacks, that emerged during the history of the development and application of this charge in various law systems, have lead to the creation of different compensational mechanisms, which also will be discussed in this article.